Systematic Literature Review : Gender Focal Point in Military - Aprillia, Bunga; Oktaviani, Jusmalia (Future Science, 2024)
Gender equality in the military is a phenomenon that still receives little attention, because the military world is still dominated by male masculinity and there is still little involvement of women in military operations or peace missions. Since the existence of UN Resolution 1325, it has become an opening for gender equality in the military world, especially for women. Women have an important role in conflict management, conflict prevention and can be peacemakers after conflict. Women are considered more sensitive to local situations and environments, thus facilitating acceptance in society. This research is descriptive research using the Systematic Literature Review (SLR) method. Based on the Scopus search results, 2 documents were found that were relevant to the gender focal point and 1 article was found from the publish or perish search results. And there are 6 previous articles that also researched gender focal points. The research results show that gender focal point research in the military field is still rare and this provides wider space for researchers interested in this field.